Preservation of Tuan Guru Sapat's Tomb through the Introduction of Constitutional Law in Village Festivals - Azhar, Ali; Fikri, KMS Novyar Satriawan; Apriyanto, Mulono (Journal of Dedication in Community, 2023)
Teluk Dalam Village has a unique cultural potential due to its history and culture, which reveal a religious leader in Riau's past. However, the region needs to be able to manage the tourism potential or earn cash from it adequately. The team designed cultural preservation initiatives through community support programs to discover new tourist attractions, preserve and document historic structures and artifacts, and package tourist attractions for performances at village festivals. The employment of debriefing, coaching, and training is employed to aid. After that, attractions are advertised via social media. The results of the mentorship programs indicate an increase in cultural preservation knowledge, expertise, and concern, all of which impact the community's potential new sources of income. Teluk Dalam Village's village festival festivities successfully preserve historical legacies and different cultural customs.